How a Robotic Visualization System Can Facilitate Targeted Muscle Reinnervation - Brauckmann, Vesta; Mayor, Jorge R.; Ernst, Luisa; Ernst, Jennifer (Journal of Reconstructive Microsurgery Open, 2024)
Background Innovations in medical technologies have impacted surgery sustainably in the last decades. To enable and further improve microsurgical outcomes, different loupes and optic-based microscopes have been proposed in recent years. In amputation surgery continuous progress and prosthetic developments have provided amputees with an improved degree of function and quality of life.Herein, we present a 17-year-old patient who suffered a traumatic loss of the left upper limb and underwent target muscle reinnervation surgery facilitated by a three-dimensional (3D) robotic exoscope system.Methods The rerouting of the distal ends of the arm nerves (TMR) was performed in the upper limb of a traumatic transhumeral amputee patient using a 3D robotic exoscope system (RS, RoboticScope, BHS Technologies, Innsbruck, Austria). Perioperative data was collected and compared to standard. Users' perspective evaluation of the system during the surgical procedure was done using a 5-point Likert scale.Results Operation time was 311 minutes, the robotic system was used for 101 minutes. Overall users' evaluation revealed a 4.5 for the selected items on the Likert scale. The evaluation showed similar results in the evaluation of the system by the main and assistant surgeons. No special training was required beforehand. The bimanual control allowed for improved personal freedom in the surgical field at a comfortable position. The imaging of colors will need future improvements until an authentic representation of in situ structures is achieved.Conclusion Major advantages of a robotic scope 3D exoscope system are improved image quality, ergonomic position, and increased accessibility in a wider operating field due to system-implied features. Another benefit is digital documentation and simultaneous education through the possibility of capturing images and videos, as well as easy transportation in between operating rooms without risk to harm the vulnerable optic. Digital microscopes are still associated with high acquisition costs, and they are not yet implemented as standard of care due to limited experience.
Keywords: robotic surgery; computer-assisted surgery; image-guided surgery; TMR; transhumeral amputation; targeted muscle reinnervation